Grade-control outdoor turning flight of robo-pigeon with quantitative stimulus parameters - Fang, Ke; Mei, Hao; Tang, Yezhong; Wang, Wenbo; Wang, Hao; Wang, Zhouyi; Dai, Zhendong (Frontiers in Neurorobotics, 2023)
Electrical microstimulation was one of the most frequently used procedures for motor control of animal robots to date. To achieve designed accuracy, it is essential to understand each parameter of electrical microstimulations onto the specific behaviors of subjects. Especially in outdoor environments, correct stimulation parameters can ensure the safety and stability of locomotor control in the animal robot. To this end, we used the homing pigeon as the motion carrier of the animal robot on which parameters of the stimulus frequency (SF), stimulation duration (SD), and inter-stimulation interval (ISI) on the robo-pigeon were tested outdoor, evaluating correspondingly the flight turning behaviors. The results presented that 1) by appropriately increasing SF and SD, the turning angle could be significantly controlled. 2) Increasing the ISI can significantly control the turning flight radius of the robo-pigeon. 3) When the stimulation parameter was set to SF>100 Hz or SD>5 s, the success rate of turning flight control was significantly reduced. Therefore, quantifying the stimulus parameters enabled graded control of the robo-pigeon's turning angle from 15 to 55° and turning radius from 25 to 135 m. These findings can be used to optimize the stimulation strategy of the robo-pigeons and achieve precise control of their turning flight behavior outdoors. Our results suggested that the grade-control outdoor turning flight can be achieved with quantitative stimulus parameters, at least, in robo-pigeons.